Nexus Between Financial Development and Economic Growth in Malaysia. - Farhana, Binti Ismail; Rossazana, Binti Ab-Rahim; Liaw, Pei-Chin (Human Resource Management Academic Research Society, 2019)
Financial development is the key for economy evolution as financial intermediaries could foster productivity growth and capital accumulation which lead to the economic growth. The nexus between financial and economic growth is an issue that has long been debated. On the one hand, a stream of literatures offer support to the contention on the running causality from financial development towards economic growth while on the other hand, economic variables are found to foster the financial institutions. Therefore, this study aims to investigate the relationship between financial development and economic growth in Malaysia over the period of 1990 to 2013. The research methods adopted are Johansen cointegration test to check the existence of short term and long term relationship between variables used and Granger causality test to determine the relationship direction for the different variables used. The study finds evidence of a long-run relationship between financial development and economic growth, amid a running causality between economic growth to all indicators of financial development in Malaysia with the exception of financial system deposit. The results imply economic growth can be further developed as it stimulates the development of financial indicators